2018
DOI: 10.1097/dbp.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga on Attention, Impulsivity, and Hyperactivity in Preschool-Aged Children with Attention-Deficit Hyperactivity Disorder Symptoms

Abstract: Yoga was associated with modest improvements on an objective measure of attention (KiTAP) and selective improvements on parent ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 25 publications
(38 reference statements)
2
64
0
2
Order By: Relevance
“…The results demonstrate that children participating in the yoga program, in comparison to the PE and CG, improved their skills related to cognitive functions, measured by the subtests of NEPSY (Korkman et al, 1998) and NEPSY-II (Korkman et al, 2007), as well as their behavior in respect to inattention and hyperactivity, evaluated by the ADHD Rating Scale-IV (DuPaul et al, 1998). The amelioration of attention with the help of yoga in the present study is in line with previous results demonstrating that sensorimotor training enhances attention in children with (Banaschewski et al, 2001; Cohen et al, 2018) and without ADHD (Mak et al, 2018). Our results are also coherent with previous studies reporting that school-based prevention programs focusing on yoga or sensorimotor training for young children can reduce deficits in attention and improve academic performance (Paour and Cèbes, 2001; Chevalier and Simard, 2006; Krisanaprakornkit et al, 2010; Gothe et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results demonstrate that children participating in the yoga program, in comparison to the PE and CG, improved their skills related to cognitive functions, measured by the subtests of NEPSY (Korkman et al, 1998) and NEPSY-II (Korkman et al, 2007), as well as their behavior in respect to inattention and hyperactivity, evaluated by the ADHD Rating Scale-IV (DuPaul et al, 1998). The amelioration of attention with the help of yoga in the present study is in line with previous results demonstrating that sensorimotor training enhances attention in children with (Banaschewski et al, 2001; Cohen et al, 2018) and without ADHD (Mak et al, 2018). Our results are also coherent with previous studies reporting that school-based prevention programs focusing on yoga or sensorimotor training for young children can reduce deficits in attention and improve academic performance (Paour and Cèbes, 2001; Chevalier and Simard, 2006; Krisanaprakornkit et al, 2010; Gothe et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are also coherent with previous studies reporting that school-based prevention programs focusing on yoga or sensorimotor training for young children can reduce deficits in attention and improve academic performance (Paour and Cèbes, 2001; Chevalier and Simard, 2006; Krisanaprakornkit et al, 2010; Gothe et al, 2013). In addition, our results support findings of previous research demonstrating that yoga practice decreases ADHD symptoms in preschool children (Cohen et al, 2018). Although, no manifest ADHD diagnosis (e.g., from a clinician, psychologist, or pediatrician) was evident for participants of the present study, many participants showed symptoms of inattention, hyperactivity, and impulsivity at T 0 (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In several early observational studies [ 22 , 23 , 24 , 25 , 26 ] with cross-sectional design, the results showed that Tai Chi/Yoga has the potential to enhance HRV through increased parasympathetic modulation [ 22 , 23 ] and/or to reduce sympathetic activity [ 24 , 25 , 26 ]. To further substantiate the potential beneficial effect of prolonged Tai Chi/Yoga training for autonomic nervous function, a growing number of experimental studies have recently been conducted [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. As the number of trials increases, two research groups attempted to systematically evaluate the existing literature regarding the effects of Tai Chi [ 34 ] or Yoga [ 35 ] on HRV.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 1115 records screened after removing duplicates, 80 full-text articles were assessed for eligibility. A total of 17 studies underwent data extraction, and 16 separate trials [ 15 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were eventually included in the final systematic review described below.…”
Section: Resultsmentioning
confidence: 99%